Derrida and other animals : the boundaries of the human - Still, Judith, 1958- (Edinburgh University Press, 2015)
Analyses Derrida's late writings on animals, especially his seminars The Beast and the Sovereign. What is man? This book examines Derrida's contribution to this long-standing philosophical and political debate, which has typically evoked a significant division between human beings and other animals. Derrida pays close attention to how animals are used to explore humanity in a range of writings, including fables and fiction. This leads to ethical questions about how humans treat animals: sacrificing animals (say, in factory farms) while extending love to pets. And it leads to political questions about how we dehumanise 'outsiders', from historical matters such as colonialism and slavery to contemporary issues such as State Terror in response to 'rogue states'. Key Features. One of the first books to make extensive reference to the two recently published volumes of Derrida's seminar series The Beast and the Sovereign Pays particular attention to Derrida's intertexts, such as Defoe, Hobbes, La Fontaine, Rousseau, Agamben and Heidegger Two chapters explore contemporary women's animal fictions, and imagined metamorphoses, looking at work by Carter, Cixous, Darrieussecq, Duffy, NDiaye, Tsvetaeva and Vivien